Evaluation of remote pulmonary function testing in motor neuron disease. Issue 5 (3rd July 2019) - Geronimo, Andrew; Simmons, Zachary
Abstract: Introduction : Motor neuron disease (MND) causes respiratory insufficiency, which is managed in part through use of noninvasive ventilation (NIV). Guidelines for the initiation of NIV are based on pulmonary function tests (PFTs), usually performed once every three months. In the setting of MND telemedicine, remote monitoring of respiratory health may permit earlier intervention, but proof of equivalence to conventional PFTs is lacking. Methods : We implemented delivery of remote PFTs (rPFTs), based on our institution's telemedicine platform, with the goals of validating measurement equivalence to conventional forced vital capacity (FVC) and maximal inspiratory pressure (MIP) assessments, and assessing process acceptability from both patients and therapists. Results : When remotely guided by a respiratory therapist, 40 patient/caregiver teams produced respiratory parameters that were tightly correlated with those acquired through the standard evaluation. Both patients and therapists generally rated the setup and use of the devices positively, with patient ratings higher than those of the therapists. Discussion : This study suggests that rPFTs are accurate and acceptable, and thus may be incorporated into MND telemedicine for clinical and research use.